Long-term results of open repair of popliteal artery aneurysm. Issue 1 (March 2015) - Wagenhäuser, M.U.; Herma, K.B.; Sagban, T.A.; Dueppers, P.; Schelzig, H.; Duran, M.
Abstract: Introduction: Popliteal artery aneurysms (PAA) are rare. Different surgical techniques for open surgical repair are possible. This study presents a single centre experience using open surgical repair with a medial approach (MA) and outlines differences between symptomatic (SLS) and asymptomatic (ALS) legs. Methods: Data collection was performed retrospectively. The investigation period was from 1 January 1996 to 1 January 2013. Patients presented in the Outpatient Department and received a questionnaire concerning their quality of life. Data are presented as mean ± standard deviation. Mann–Whitney test and Cochran–Armitage test for trend was used for data analysis. Kaplan–Meier method was used to calculate limb salvage rates. p  < 0.05 was considered statistically significant. Results: We analyzed 16 ALS and 26 SLS with an average age of 63.5 ± 10 years. Preoperative ankle-brachial index (ABI) was 1.0 ± 0.2 for ALS (on control examination: 1.12 ± 0.24) and 0.08 ± 0.18 for SLS (on control examination 0.94 ± 0.14) ( p  < 0.05). Limb salvage rate was 100% for ALS and 86.7% for SLS (overall 93.3%). Primary patency rate for SLS was 85%, for ALS rate of 100%, respectively (overall 92.5%). ALS reached an average of 13.1 ± 2.7 points (SLS 11.4 ± 2.8) on a numeric point scale. Conclusion: Open surgery is therapy and prevention of acute ischaemia all in one, especially for asymptomatic patients and delivers good long-term results. Endovascular therapies offer an alternative but long-term results are pending. Open surgery should still be considered as a gold standard therapy. Highlights: 30 day Primary patency rate: 100% asymptomatic legs; 92% for symptomatic legs. Better life quality for asymptomatic legs in the follow-up. Better ankle-brachial index for asymptomatic legs on control examination.